La hora de la estrella - Lispector, Clarice; Poljak, Ana; Lispector, Clarice (Madrid : Siruela, 2015)
In a haunting psychological tale of despair and freedom, Macabea is ugly, underfed, sickly, and unloved yet she fascinates Rodrigo because she is unaware of how unhappy she should be.
Online resource; title from ePub title page (Digitalia, viewed April 21, 2017)
Keywords: Rio de Janeiro (Brazil) -- Fiction; Psychological fiction; Electronic books